REPRESENTATION OF SUBALTERNITY IN ARUNDHATI ROY’S THE GOD OF SMALL THINGS - Kaur, Rupinder (International Journal of Psychosocial Rehabilitation, 2020)
Arundhati Roy (born November 24, 1961, Shillong, Meghalaya, India) an Indian author and political activist, is best known for her Booker award-winning novel The God of Small Things (1997) and for her involvement in environmental and human rights issues. The novel composed in an unconventional plot, using multiple techniques and a lyrical language for dealing with subaltern issues, Roy’s novel won the 1997 Man Booker Prize for Fiction and became the bestselling book. The present paper seeks to explore the subalternization of women and the Untouchables in Arundhati Roy’s The God of Small Things (1997). It highlights the subordinated, marginalized condition of a person due to their belonging to the periphery of society. The maltreatment of the subaltern is the major issue. The novel depicts the condition of the untouchables and women in India, especially in Kerala. In Kerala, untouchability is prevalent more than elsewhere in India, and is not restricted to Hindus only, but Christians practice these rules and customs also. The paper will explore the theme of the subalternization of women and the Untouchables by analyzing three main female characters in the novel: Mammachi, Ammu, and Rahel and male character Velutha, an Untouchable in the lingering caste system of India.